Hubungan Koordinasi Mata dan Kaki dan Keseimbangan dengan Kemampuan Akurasi Shooting Sepakbola pada Tim SMA Negeri 1 Sabak Auh - Syaputra Syaputra; Kristi Agust; Syahriadi Syahriadi (Journal on Education, 2024)
The aim of this research is to determine the relationship between eye-foot coordination and balance with shooting ability in the Sabak Auh 1 State High School team. The population in this study was the SMA Negeri 1 Sabak Auh team. Based on information from the coach of SMA Negeri 1 Sabak Auh, there are 22 players registered and actively practicing. The instruments in this research were tests including an eye and foot coordination test using an eye and foot coordination test, a balance test using a balance test and a shooting test using a goal shooting accuracy test. Based on the results of the research that the author has described in the previous chapter, the following conclusions can be drawn: From the results obtained, eye and foot coordination has a low correlation with shooting results in the football game of the Sabak Auh State High School 1 Team, namely the acquisition of rcount (0.257) < from the rtable gain (0.433) at α=0.05. From the results obtained for balance there is a very low relationship with the shooting results in the soccer game of the Sabak Auh State High School 1 team, namely the rcount gain (0.097) < from the rtable gain (0.433) at α = 0.05. There is a low correlation between balance and eye and foot coordination on shooting results in the football game of the Sabak Auh 1 State High School team, namely the Rcount (0.258) < the Rtable (0.433) at α = 0, 05.